Comparison of the Effectiveness of Creativity Therapy Training and Group Counseling Based on Choice Theory on Students’ Motivation Improving - Yousefi Jooybari, Fahime; Hassanzadeh, Ramazan; Fakhri, Mohammad Kazem (International Clinical Neuroscience Journal, 2018)
Background: According to findings educational psychologist's motivation has important effect upon student's achievement and performance. Therapists and psychologists have tried to study the methods of motivation improving in students. Objective: The present study compares the effectiveness of creativity therapy training and group counseling based on the choice theory on motivation improving in students. Methods: The participants of this study included all students referring to the counseling center of Payam Noor University, Sari center, in the academic year of 2016-2017. The convenience sampling method was used for the selection of all the subjects. The sample consisted of 45 individuals who were randomly divided in to three experimental and control groups (15 individuals per group). In pre-test, the motivation improving questionnaire was administered for all groups. The experimental groups received the training of creativity therapy and group counseling based on the theory of choice in 8 (90 minutes) sessions for 2 months. The control group did not receive training during this period. After completing the training, post-test was obtained in three groups. Data were analyzed using covariance analysis by the spss-16. Results: The results showed that there is a significant difference between the effectiveness of creativity therapy training and group counseling based on choice theory in promoting students motivation (p˂0.05). Also, group counseling based on choice theory had more effect upon students motivation improving than creativity therapy (p=0.001). Conclusion: creativity therapy training and group counseling based on choice theory may be effective in improving motivation in students.